Effects of age on physiological, immunohistochemical and biochemical properties of fast-twitch single motor units in the rat. - Larsson, L (1991)
1. Physiological, enzyme-histochemical, biochemical and morphometrical properties of fast-twitch single motor units were compared between young (3-6 months) and old rats (20-24 months) using the glycogen depletion technique. Monoclonal antibodies (mAbs) were used to identify the myosin heavy chain (MHC) composition in the muscle fibres of the motor unit (motor unit fibres) in order to facilitate correlative physiological, histochemical, biochemical and morphometrical studies. 2. Earlier observations on effects of age on contractile properties of fast-twitch motor units were confirmed and extended. That is, the duration of the isometric twitch, and the twitch and tetanus forces, were increased. Further, motor unit fibres were rearranged, occupying a larger territory and displaying an increased innervation ratio in old age, indicating a denervation-reinnervation process. 3. Motor units with muscle fibres expressing the novel IIX myosin heavy chain (MHC) were observed in both young and old animals, and they constituted the predominant motor unity type identified in the old animals. In contrast to the type IIX MHC motor units in the young animals, the type IIX MHC units in old age often contained muscle fibres which expressed either the type IIA or type IIB MHC, although type IIX MHC fibres were in the majority (so called 'IIX' MHC motor units), but motor units containing all these three fibre types were never observed. There were also single fibres co-expressing IIX and IIB MHCs in old age. 4. In the young animals the IIX MHC motor units had a higher (P less than 0.001) resistance to fatigue (fatigue ratio 0.45 +/- 0.11) than the type IIB MHC units (0.03 +/- 0.05), a succinate dehydrogenase (SDH) activity (0.62 +/- .007) intermediate (P less than 0.001) between those of type IIA muscle fibres classified according to myofibrillar ATPase activity after acid pre-incubation, i.e. type IIA ATPase, (0.84 +/- 0.13) and type IIB MHC motor unit fibres (0.20 +/- 0.04), and cross-sectional fibre areas (1650 +/- 320 microns 2) which were similar to those of type IIA ATPase muscle fibres (1460 +/- 150 microns 2) but smaller (P less than 0.001) than type IIB MHC motor unit fibres (4650 +/- 1180 microns 2).(ABSTRACT TRUNCATED AT 400 WORDS)